2016
DOI: 10.1007/s11060-016-2208-8
|View full text |Cite
|
Sign up to set email alerts
|

A cure is possible: a study of 10-year survivors of brain metastases

Abstract: Little is known on the natural history, recurrence patterns, neurocognitive outcomes and prognostic factors associated with survival in long-term survivors (≥10 years) from brain metastasis (BM). In this study, the records of 1953 patients who underwent treatment for BM with a potential for ≥10 years of follow-up were reviewed. Cox regression analysis identified factors predictive for overall survival (OS). The median age at brain metastasis diagnosis was 60 years and the median OS was 6.4 months. The 1-year O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 26 publications
1
8
0
2
Order By: Relevance
“…In most studies, rates of OS among LTS were relatively stable during the three to five years following BM diagnosis. Furthermore, Kotecha et al reported that 41% of patients who survived at least five years were alive at 10 years [17]. In our study, 42 patients were alive and without active disease at their last follow up.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In most studies, rates of OS among LTS were relatively stable during the three to five years following BM diagnosis. Furthermore, Kotecha et al reported that 41% of patients who survived at least five years were alive at 10 years [17]. In our study, 42 patients were alive and without active disease at their last follow up.…”
Section: Discussionsupporting
confidence: 51%
“…Intracranial disease burden is an important prognostic factor for BM patients [11][12][13]17]. In our cohort, 65% of LTS had a single metastasis.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…While cognitive decline secondary to radiation therapy is a problem that continues to be studied, understanding and solving this problem is difficult for several reasons: (1) wide variations in age, treatment technique, tumor types, and cognitive performance scoring make generalizations difficult, (2) most patients are not cured and thus competing sources of cognitive decline such as tumor progression and further chemotherapy confound most analyses, and (3) radiation oncologists are increasingly utilizing the technique of stereotactic radiosurgery (SRS) over whole brain radiotherapy (WBRT) which minimizes dose to the healthy brain, thus limiting the pool of patients that would be best for studying cognitive decline [33,34,35,36,37,38,39,40,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, gamma knife radiosurgery (GKRS) has been increasingly used for intracranial lesions [14]. In Taiwan, the up-to-date official information indicates that there are seven gamma knife units and about 1100 patients undergo GKRS every year.…”
Section: Introductionmentioning
confidence: 99%